Confucian justification of leadership democracy: a distinction between Confucian ethics and politics - Jin, Y (2021)
My doctoral study focuses on the relationship between classic Confucian thought and democratic theory, examining whether canonical Confucian texts in the pre-Qin period (770-221 BC), especially the Analects, the Mencius and the Xunzi, can provide intellectual sources of justification for democracy. In Confucian political theory today, there is a crucial debate on whether the stretch of Confucian thought can lend support to democracy. Examining the relationship between Confucianism and democracy not only helps to clarify different flavors of Confucianism to which various normative theories subscribe, but also has a crucial bearing on envisioning ways in which the Confucian tradition can be renewed under modern conditions.